Optimization and functional properties of ginseng root extract in Chyawanprash - Soni, Akanksha; Pant, Prity; Mishra, R C; Chaudhary, Neetu; Devi, Shalini (Journal of Postharvest Technology, 2022)
In addition to being employed as therapeutic agents, ginseng roots are now sold as nutritional supplements and as a raw material for health foods. The  main aim of this study was to determine the total ginsenoside, total polyphenol, total flavonoid content, and antioxidant activity of ginseng root extract.  The optimization of ginseng root extract was also done in Chyawanprash. Traditional ginseng medicines and food supplements are the most popular  herbal products worldwide. The total ginsenoside, polyphenol, flavonoid content were found as 36.29±0.01, 31.24±1.22, 21.17±0.2 respectively. The  DPPH & ABTS radical scavenging activity were investigated as 46.33±0.01 and 40.21±0.00 in Ginseng root extract. The treatment sample T3 had 1.0  percent ginseng root extract, given the highest score for taste and flavour by sensory panellists. Finally, the Chyanwanprash with additional functional properties and specific flavour was successfully developed.
Keywords: Chyawanprash; ginseng root extract; ginsenoside; polyphenol,; flavonoid